1977
DOI: 10.1073/pnas.74.8.3365
|View full text |Cite
|
Sign up to set email alerts
|

Opiate-dependent modulation of adenylate cyclase.

Abstract: Reactions mediated by the opiate receptors that inhibit adenylate cyclase (EC 4.6 (1-3). However, exposure of cells to an opiate for 12 or more hours results in a compensatory increase in adenylate cyclase activity that is long-lived and not readily reversed by withdrawal of the opiate (4-6). Similar dual regulations of adenylate cyclase activity are mediated by a-adrenergic receptors (7) and excitatory muscarinic acetylcholine receptors (S. K. Sharma and M. Nirenberg, unpublished data; ref. 8). Thus, dual r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
99
1
1

Year Published

1981
1981
2009
2009

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 215 publications
(101 citation statements)
references
References 16 publications
0
99
1
1
Order By: Relevance
“…The reduction in cAMP levels during the agonist opiate exposure could initiate a cascade of cellular changes, which could lead to up-regulation of the amount and/or activity of AC [7,20]. Enhanced coupling of the stimulatory PGEj receptor to Gs or elevated levels of functionally intact Gs proteins were proposed by Ammer and Schulz [4,5] for opioid-treated NG108-15 and SH-SY5Y cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reduction in cAMP levels during the agonist opiate exposure could initiate a cascade of cellular changes, which could lead to up-regulation of the amount and/or activity of AC [7,20]. Enhanced coupling of the stimulatory PGEj receptor to Gs or elevated levels of functionally intact Gs proteins were proposed by Ammer and Schulz [4,5] for opioid-treated NG108-15 and SH-SY5Y cells.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic activation of opioid receptors in NG108-15 neuroblastoma x glioma cell line (containing g-receptors), as well as in the human neuroblastoma SH-SY5Y (containing mainly preceptors and some g-receptors), followed by the withdrawal of the opioid agonist, was shown to lead to AC supersensitivity ('overshoot') [4][5][6][7][8]. It has been suggested that this phenomenon represents a possible cellular adaptation mechanism associated with chronic opioid exposure.…”
Section: Introductionmentioning
confidence: 99%
“…Since the first characterization of cellular responses to EtOH (10) and other commonly abused drugs (11), molecules involved in G protein signaling have received much attention in the addiction literature (cf. refs.…”
mentioning
confidence: 99%
“…In mammalian cells, opioid receptors couple to inhibitory G proteins of the G i/o family and inhibit the adenylyl cyclase [22]. Agonists DAGO and Ohm inhibited 10 μ M forskolin-stimulated increase in intracellular cAMP production in a dose-dependent manner with IC 50 values of 0.9 nM and 0.3 nM, respectively (Fig 4A).…”
Section: Hμor Functionally Coupled To Endogenous Gi/o Proteinsmentioning
confidence: 94%